2006
DOI: 10.1300/j079v33n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Residential Trajectories of Participants in North Carolina's Willie-M. Program

Abstract: A semi-parametric mixture model was fit using data on 611 children with serious emotional disturbance who participated in North Carolina's Willie-M. Program from 1995 to 2000 to identify patterns of residential restrictiveness over time. Results revealed 4 distinct restrictiveness trajectories: low/stable, high/stable, increasing, and decreasing. Correlates of trajectory group membership included age, IQ, initial behavior, and region of the state. Number of diagnoses and change in behavior did not predict grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In spite of the skepticism about their continued use (Dishion, Dodge, & Lansford, 2008), these settings have remained an integral component of the system of services for youth (Geller & Biebel, 2006; McCurdy & Mclntyre, 2004). This is supported by some research evidence that group homes and residential treatment centers care for children with greater treatment needs (Nash, Thompson, & Kim, 2006; Preyde, Adams, Cameron, & Frensch, 2009), and continue to be the most frequently utilized placements within the continuum of intensive and restrictive services available (James et al, 2006; McMillen et al, 2004). …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In spite of the skepticism about their continued use (Dishion, Dodge, & Lansford, 2008), these settings have remained an integral component of the system of services for youth (Geller & Biebel, 2006; McCurdy & Mclntyre, 2004). This is supported by some research evidence that group homes and residential treatment centers care for children with greater treatment needs (Nash, Thompson, & Kim, 2006; Preyde, Adams, Cameron, & Frensch, 2009), and continue to be the most frequently utilized placements within the continuum of intensive and restrictive services available (James et al, 2006; McMillen et al, 2004). …”
Section: Introductionmentioning
confidence: 87%
“…For the most part, researchers have found a high level of correspondence between youth problems and the restrictiveness of the setting in which they receive care (Handwerk, Friman, Mott, & Stairs, 1998; Nash et al, 2006), although this is not always the case (Fields & Ogles, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Other investigators indicate that youth served by more restrictive residential programs have greater emotional and behavioral needs than youth receiving less restrictive community- or family-based care (Briggs et al, 2012; Handwerk et al, 1998; Nash, Thompson, & Kim, 2006; Pottick, Warner, & Yoder, 2005). The preceding studies report that youth across various residential programs (e.g., acute care shelter, group homes, wilderness program, or residential treatment center) have high rates of externalizing and internalizing behavior problems, academic problems, comorbid diagnoses, substance use problems, suicidal or self-injurious behavior, and trauma, including abuse or neglect.…”
Section: Match Between Clinical Needs and Level Of Carementioning
confidence: 99%
“…Some studies have indicated that movement to a more restrictive placement and an increase in the severity of behavior problems are correlated (Handwerk, Friman, Mott, & Stairs, 1998; Huefner, James, Ringle, Thompson, & Daly, 2010; Nash, Thompson, & Kim, 2006). Yet there is also countervailing evidence that a substantial number of children placed into the most restrictive settings have needs that are no more severe than those of children in lower level family-based care (Breland-Noble, Farmer, Dubs, Potter, & Burns, 2005; Farmer, Mustillo, Burns, & Holdern, 2008; James, Roesch, & Zhang, 2011; Lyons, Libman-Mintzer, Kisiel, & Shallcross, 1998).…”
Section: Introductionmentioning
confidence: 99%